Renewable electricity targets in selected MENA countries: Assessment of available resources, generation costs and GHG emissions - Sebastian Timmerberg; Anas Sanna; Martin Kaltschmitt; Matthias Finkbeiner (Energy Reports, 2019)
MENA countries published national policy targets for the implementation of electricity from renewable energy (RE). These targets are important as they serve as framework for stakeholders in the energy sector like businesses and administration, while also showing governmental ambitions to the public. This paper investigates the impact on resources, generation cost and GHG emissions if the targets are met. It also examines whether the current development is achieving the targets and how the targets perform in the light of the Paris Agreement. 13 to 52 % of electricity from RE is targeted for 2030. The necessary RE expansion exceeds the current expansion in most countries. Only in Morocco and Jordan are projects indicating that the targets might be reached. From a resource perspective, a much stronger expansion is possible. Beneficial locations exist allowing to cover the domestic demand or even an export of electrical energy or derived energy carrier. Furthermore, especially PV, but also wind systems, can generate electricity in many areas for lower cost than fossil fuel fired power plants. Specific GHG emissions of national electricity production in 2017 are estimated to 396-682 gCO2e/kWh and decrease to 341-514 gCO2e/kWh if the 2030 RE targets are met. The type of fossil fuel has a strong impact on the GHG emissions. Although Morocco has highest RE deployment today and targets highest RE share in 2030, it shows today and in 2030 specific GHG emissions that are among the highest of considered MENA countries because electricity production from coal dominates whereas other countries use mainly natural gas. Existing policy targets decrease specific GHG emissions until 2030. However, stronger GHG mitigation efforts will be necessary afterwards in order to reach targets of the Paris Agreement. More ambitious 2030 policy target would distribute the load more evenly over time and should be reconsidered.
Keywords: 330